انحلال تيتانات الديسبروزيوم في مصهورة أكاسيد البزموت والبور (Latakia University Journal -Basic Sciences Series, 2018)
تمّت دراسة القوانين الحركيّة لعمليّة انحلال تيتانات الديسبروزيوم في مصهورات أكاسيد بزموث-بور بطريقة القرص الدوّار. قمنا في هذه الدراسة بتحديد مجال نظام الانتشار, كما حدّدنا عوامل الانتشار التي تصف عمليّة انتقال التيتانيوم والديسبروزيوم من الطور الصلب إلى المصهورة. استخدمت طرائق التحليل الآليّ لتحديد التيتانيوم والديسبروزيوم في تيتانات الديسبروزيوم الداخلة في تركيب العيّنات الزجاجيّة القياسيّة المستخدمة كعيّنات مقارنة ولتأكيد صحّة التقنية التي استُخدمت في عمليّة تصنيع هذه العيّنات. بيّنت الدراسة التحليليّة باستخدام طرائق انبعاث وفلورة أشعّة رونتجن من أجل تحليل العناصر المشار إليها في العيّنات القياسيّة بأنّ خطأ نتائج التحليل لا يزيد عن 0.05 ضمن حيّز واسع لمحتوى هذه العناصر.   A study of the kinetic laws of the dissolution of dysprosium titans in bismuth-boron oxides fuses was carried out with rotary disc. In this study, the field of diffusion system was defined. Parameters of diffusion, which describe the process of transformation of titanium and dysprosium from the solid phase to the fuse, were also defined. Mechanical analysis methods were used to define the titanium and the dysprosium in the dysprosium titans included in the composition of the standard glass samples used as comparative samples, and to confirm the correctness of the technique used in the manufacturing process of these samples. The analytical study using luminescence and fluorescence of Roentgen rays to define the above-mentioned elements in the standard samples has shown that the error in the results of the analysis is not more than 0,05 within a wide range of the content of these elements.